A Qualitative Framework of Teacher-Mediated Fine Motor Skill Scaffolding in Low-Resource Early Childhood Settings - Ahmed Ademola Oyeyemi; Pascal Roubides; Ronato S. Ballado; Vanessa Vinodhen; Workineh Kebede; Tlalane Mosae; Ryan Angga Pratama; Onesme Niyibizi (Nak-Kanak: Journal of Child Research, 2026)
Background of the study: Fine motor development is essential for early academic readiness, autonomy, and self-confidence. Although prior research emphasizes its importance, limited attention has been given to how teachers scaffold fine motor skills in low-resource early childhood settings, where access to standardized materials is often constrained. Aims and scope of paper: This study aims to develop a qualitative framework explaining how teachers scaffold fine motor development through everyday instructional practices in low-resource early childhood settings. It examines strategies for assessing children’s abilities, adapting learning activities, and using locally available materials to address developmental variability among children aged 5–6 years. Methods: A qualitative descriptive approach was employed at Kindergarten Anugerah, an early childhood education institution. Data were collected through classroom observations and semi-structured interviews with early childhood teachers. Observational data captured real-time learning activities and teacher–child interactions, while interviews elicited teachers’ pedagogical reasoning and professional reflections. Data were analyzed using an interactive thematic analysis model to identify recurring patterns and instructional practices. Results: The findings indicate that teachers actively engage in diagnostic observation to identify variations in children’s fine motor development. Instructional scaffolding was implemented through the adaptive use of low-cost and locally available materials, including beach sand, modeling clay, textured objects, and art-based activities such as tearing, folding, and collage-making. Teachers emphasized creativity, hands-on engagement, and flexible instructional responses as key mechanisms for supporting children with delayed fine motor skills. Contribution: This study develops a qualitative framework of teacher-mediated fine motor scaffolding in low-resource early childhood settings. The framework explains how assessment, material adaptation, and responsive instruction interact to support fine motor development. By foregrounding the role of educators in resource-constrained environments, the study extends fine motor pedagogy beyond resource-rich contexts and provides transferable insights for early childhood education in the Global South.